Experimental Study On Effect Of End Plate Thickness On Moment Capacity And Failure Mode Of RC Square Pile Joints - Chan, Han Pin (Universiti Sains Malaysia, 2005)
Precast reinforced concrete pile length is generally limited to 12 meters due to transportation and handling constraints. Pile joints are needed to lengthen the pile for certain circumstances where pile length exceeding 12 meters is needed. The joints strength should not be less than in all respects to that of the pile section joined. The components of RC square pile joint consist of pile end plate, centering bar, anchor bar and mild steel skirting. The objective of this final year project is to further investigate by means of experiment on the effect of end plate thickness on capacity at both serviceability and ultimate limit states and failure mode of RC pile joints at ultimate limit state. The result obtained shows that increasing of end plate thickness will lead to the higher moment capacity of the pile joints as follows: 4.624 kN m (4 mm end plate), 7.208 kN m (6 mm end plate) and 10.374 kN m (8 mm end plate). The failure modes of specimens differ for different end plate thickness. For the case of 4 mm end plate thickness, specimen failure mode is caused by the local excessive bending at welded connection between anchor bar and the end plate. For 6 mm end plate thickness specimen, the failure mode is mainly due to pull-out failure. Meanwhile, the failure mode for the 8 mm case is classified as failure of RC section.